Margin negative resection and pathologic downstaging with multiagent chemotherapy with or without radiotherapy in patients with localized pancreas cancer: A national cancer database analysis. (March 2021) - Miccio, Joseph A.; Talcott, Wesley J.; Patel, Timil; Park, Henry S.; Cecchini, Michael; Salem, Ronald R.; Khan, Sajid A.; Stein, Stacey; Kortmansky, Jeremy S.; Lacy, Jill; Narang, Amol; Herman, Joseph; et al.
Highlights: Complete resection is a potentially curative treatment for pancreatic cancer. This report studies neoadjuvant chemotherapy with or without radiation. The addition of radiation was associated with improved complete resection rates. The addition of radiation was associated with improved pathologic down staging. Abstract: Purpose: Margin-negative (R0) resection is the only potentially curative treatment for patients with pancreatic ductal adenocarcinoma (PDAC). Pre-operative multi-agent chemotherapy alone (MAC) or MAC followed by pre-operative radiotherapy (MAC + RT) may be used to improve resectability and potentially survival. However, the optimal pre-operative regimen is unknown. Methods: Patients with non-metastatic PDAC from 2006 to 2016 who received pre-operative MAC or MAC + RT before oncologic resection were identified in the National Cancer Database. Univariable and multivariable (MVA) associates with R0 resection were identified with logistic regression, and survival was analyzed secondarily with the Kaplan Meier method and Cox regression analysis. Results: 4, 599 patients were identified (MAC: 3, 109, MAC + RT: 1, 490). Compared to those receiving MAC, patients receiving MAC + RT were more likely to have cT3-4 disease (76% vs 64%, p < 0.001) and cN + disease (33% vs 29%, p = 0.010), but were less likely to have ypT3-4 disease (59% vs 74%, p < 0.001) and ypN + disease (32% vs 55%, p < 0.001) and more likely to have a pathologic complete response (5% vs 2%, p < 0.001) and R0 resection (86% vs 80%, p < 0.001). On MVA, MAC + RT (OR 1.58, 95% CI 1.33–1.89, p < 0.001), evaluation at an academic center (OR 1.33, 95% CI 1.14–1.56, p < 0.001), and female sex (OR 1.43, 95% CI 1.23–1.67, p < 0.001) were associated with higher odds of R0 resection, while cT3-4 disease (OR 0.81, 95% CI 0.68–0.96, p = 0.013) was associated with lower odds of R0 resection. Conclusion: For patients with localized PDAC who receive pre-operative MAC, the addition of pre-operative RT was associated with improved rates of R0 resection and pathologic response.